2016
DOI: 10.1038/srep25200
|View full text |Cite
|
Sign up to set email alerts
|

Coding deficits in hidden hearing loss induced by noise: the nature and impacts

Abstract: Hidden hearing refers to the functional deficits in hearing without deterioration in hearing sensitivity. This concept is proposed based upon recent finding of massive noise-induced damage on ribbon synapse between inner hair cells (IHCs) and spiral ganglion neurons (SGNs) in the cochlea without significant permanent threshold shifts (PTS). Presumably, such damage may cause coding deficits in auditory nerve fibers (ANFs). However, such deficits had not been detailed except that a selective loss of ANFs with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
104
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 32 publications
8
104
0
1
Order By: Relevance
“…In both mice (Liberman et al, 2015) and guinea pigs (Furman et al, 2013; Song et al, 2016), surviving ribbons in noise-damaged regions were often larger than normal. Surviving ribbons were also hypertrophied in the noise-exposed macaques (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In both mice (Liberman et al, 2015) and guinea pigs (Furman et al, 2013; Song et al, 2016), surviving ribbons in noise-damaged regions were often larger than normal. Surviving ribbons were also hypertrophied in the noise-exposed macaques (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, comparable noise-exposure studies in guinea pigs have suggested that, after an initial reduction in the number of presynaptic ribbons, the synapse count may largely recover (Liu et al., 2012, Shi et al., 2013). It appears as though these synapses are reformed to some degree, but although they are present, their coding properties are functionally abnormal, both in their amplitude and latency profiles (Song et al., 2016). These studies suggest clear differences in the manifestation of cochlear synaptopathy in the guinea pig compared to the mouse and they also report ribbon damage to high-SR units as well as the more widely demonstrated loss of low-SR fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Noise-induced synaptopathy in guinea pigs requires higher sound levels than in mice and long-term degeneration of spiral ganglion cells is less pronounced (Lin et al., 2011). In stark contrast with mouse data, guinea pig synapses damaged by noise appear largely repairable (Liu et al., 2012, Shi et al., 2013), leading to only transient changes in the distribution of spontaneous rates among AN fibers (Song et al., 2016). Early indications from a macaque model suggest that primates may exhibit even greater resistance to noise-induced synaptopathy (Burton et al., 2016).…”
Section: Discussionmentioning
confidence: 99%